Minimally Invasive Adenocarcinoma of the Lung as Second Malignant Neoplasm Following Pediatric Rhabdomyosarcoma. Issue 2 (14th July 2015) - Bradee, Allison R.; Lehman, Alice; Reed, Robyn C.; Watson, Andrea; Acton, Robert
Abstract : Primary pulmonary tumors are extremely rare in the pediatric population; however, sporadic cases of invasive pulmonary adenocarcinoma as a second malignant neoplasm (SMN) have been described in survivors of pediatric cancers. Pediatric patients with rhabdomyosarcoma (RMS) have a particularly increased risk of developing a SMN when compared to the general population, though pulmonary adenocarcinoma has not been previously described in a RMS patient. A 12‐year‐old female previously treated for stage IV pelvic RMS was found to have a left pulmonary nodule on surveillance computed tomography. The nodule was detected 4.25 years after the completion of treatment, which included resection, chemotherapy, and radiation to the abdomen and pelvis. Wedge resection of the pulmonary lesion was performed with negative margins. Histopathological examination revealed minimally invasive adenocarcinoma. Pulmonary adenocarcinoma may rarely present as a SMN in pediatric cancer survivors. The pathogenesis of this association is not yet entirely clear, but may include chemotherapy‐induced mutagenesis and/or genetic predisposition. As pulmonary adenocarcinoma may present as a lung lesion radiographically indistinguishable from metastatic RMS, it should be considered in the differential diagnosis of any pediatric RMS survivor presenting with a new pulmonary nodule, especially in cases with late recurrence. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.